Environmental Project and Enhancement of Periurban territories - Andrea Tartaglia; Davide Cerati; Guglielmo Di Chiara (Agathón)
The enhancement of peri-urban rural areas is addressed through a design experience in the southwest of the Metropolitan City of Milan based on the integration of environmental, economic-productive and sociocultural components. The experience develops an implementation model aimed at facilitating the integration of the rehabilitation practices of peri-urban rural territories in coherence with the European and regional policies for territorial development. Design simulations resulted in the conscious, pro-active and productive re-design of the rural landscape reshaping the role of abandoned buildings in a functional and performance key.